Performance of Banana Peelings Extract as A Natural Coagulant in the Treatment of Surface Water Case Study: River Rwizi, Mbarara. - Asingya, Derrick (Kabale University, 2023)
The existence of suspended solids and other pollutants in water leads to countless drawbacks during water treatment creating deleterious disinfection by-products such as trihalomethanes, Dichlorobromomethane and Trichloroacetic acid after the use of chemical coagulants, which are potentially deleterious to human health and the environment. However, many researchers have come up with different plant-based coagulants to replace Aluminum sulphate thus, the main objective of this research was to the investigate performance of banana peelings extract as a natural coagulant in the treatment of surface water by comparing the coagulation action of the raw and ripe banana peelings extracts against Aluminium sulphate, a chemical coagulant as the control experiment.